PENGARUH PAJAK, MEKANISME BONUS, PROFITABILITAS DAN EXCHANGE RATE TERHADAP KEPUTUSAN TRANSFER PRICING - Ni Ketut Sari Arik Suastini; Ni Wayan Yuniasih (UNHI Press, 2022)
Transfer Pricing policy by company to determine the transactions price among division members inside one company also among divisions member of two companies both abroadalso domestical. The research has a purposes to determine whether Taxes, Bonus Mechanisms, Profitability and Exchange Rates affect the decision making o the companyto take Transfer Pricing actions on Manufacturing companies inside the list of Bursa Efek Indonesia (BEI) at 2017 to 2019. The research’s population are companies of manufacturelisted on the Bursa Efek Indonesia (BEI) at 2017 to 2019, which amount to 154 companies. The researcher are using non-probability sampling and purposive sampling as thesampling methods. Through the specified criteria, 27 sample companies were obtained. The researcher used secondary data, namely the annual financial report archive of company from 2016 to 2019 gathered from BEI website. Researcher are using logistic regression analysis to analyze the research data.